2021
DOI: 10.3390/ijerph18063294
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Problems among Disaster Victims: A Long-Term Survey on the Life Changes of Disaster Victims in Korea

Abstract: This study aimed to assess sleep problems and their underlying factors in victims of disasters such as typhoons, heavy rains, fires, and earthquakes. Data from the long-term survey on life changes among disaster victims in 2019 obtained by the National Disaster Management Research Institute were used. The study included 1358 victims of natural and social disasters in Korea between 2012 and 2018. Sleep problems were assessed using a survey on subjective sleep quality and the use of sleeping medication. The data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
0
7
0
1
Order By: Relevance
“…In 2012 alone, there were 16 earthquakes, with magnitudes higher than level 5 (Yan, 2013). In a recent study, Kim and Lee (2021) observed that victims of typhoons, earthquakes, fires, and heavy rains tend to have higher prevalence of sleep problems. Therefore, the climate might be a determinant associated with the observed regional disparities.…”
Section: Discussionmentioning
confidence: 98%
“…In 2012 alone, there were 16 earthquakes, with magnitudes higher than level 5 (Yan, 2013). In a recent study, Kim and Lee (2021) observed that victims of typhoons, earthquakes, fires, and heavy rains tend to have higher prevalence of sleep problems. Therefore, the climate might be a determinant associated with the observed regional disparities.…”
Section: Discussionmentioning
confidence: 98%
“…Although there are no studies about the prevalence of depression in Brumadinho, a recent article reported that Brazilian rates are among the highest 31 , which explains why depressive symptoms ranked first here. Some studies, although very few, have investigated the prevalence of other psychiatric symptoms and have shown a high prevalence of generalized anxiety disorders 11,12 , sui-cide risk 12,32 , and sleep disorders 12,33 . Our study's findings agree with the literature: high prevalence of anxiety symptoms, ideas of death and self-harm, and self-reported poor sleep quality.…”
Section: Crude and Adjusted Analysesmentioning
confidence: 99%
“…Embora não seja comum, alguns estudos investigaram a prevalência de outros sintomas psiquiátricos e demonstraram elevadas prevalências para os transtornos de ansiedade generalizada 11,12 , risco de suicídio 12,32 e alterações de sono 12,33 . Dados do presente estudo estão em concordância com a literatura, indicando prevalências elevadas para sintomas ansiosos, ideias de morte e automutilação e autorrelato da pior qualidade do sono.…”
Section: Análises Brutas E Ajustadasunclassified